Globalizing Asian Religions : Management and Marketing - Ramsay, Tamasin; Matsunaga, Louella, 1959-; Nakamaki, Hirochika, 1947-; Smith, Wendy (Wendy Anne) (Global Asia (Amsterdam, Netherlands), 2019)
This book brings together the insights of theories of management and marketing to give an original view of the organizational dynamics of globalizing Asian New Religious Movements (NRMs) and established religions. Seventeen authors in this collection have recast their data on individual Asian religions and social movements to focus on the way these organizations are managed in an overseas or global context, by examining the structure, organizational culture, management style, leadership principles and marketing strategies of the religious movements they had hitherto studied from the perspective of the sociology of religion, or religious studies. The book examines strategies for global proselytization and outcomes in a variety of local ethnographic contexts, thus contributing to the scholarly work on the 'glocalization' of religions.